2023
DOI: 10.1037/edu0000712
|View full text |Cite
|
Sign up to set email alerts
|

Does being defended relate to decreases in victimization and improved psychosocial adjustment among victims?

Abstract: School bullying is a clear violation of children's rights to a safe education and is a major concern among school professionals and parents. Many antibullying interventions focus on enhancing peer defending of victims to combat bullying and to promote victims' psychosocial functioning. However, longitudinal studies on the effects of being defended on (a) diminishing victimization and (b) enhancing victims' psychosocial adjustment are lacking, and the role of the broader peer context has been largely unexplored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
(118 reference statements)
0
11
0
Order By: Relevance
“…Strikingly, a third of victims with a support group even reported that their victimization levels had increased—despite having more defenders ( van der Ploeg et al, 2016 ). A longitudinal study indicated that defended and non-defended victims (at the start of the school year) had comparable levels of victimization at the end of the school year ( Laninga-Wijnen, van den Berg, Garandeau, Mulder, & de Castro, in press ).…”
Section: Consequences Of Defendingmentioning
confidence: 99%
“…Strikingly, a third of victims with a support group even reported that their victimization levels had increased—despite having more defenders ( van der Ploeg et al, 2016 ). A longitudinal study indicated that defended and non-defended victims (at the start of the school year) had comparable levels of victimization at the end of the school year ( Laninga-Wijnen, van den Berg, Garandeau, Mulder, & de Castro, in press ).…”
Section: Consequences Of Defendingmentioning
confidence: 99%
“…On the other hand, although bystander interventions have been encouraged in antibullying programs (Salmivalli, 2014), recent evidence has put into question the capacity of defending behavior to decrease bullying and improve victims’ psychosocial functioning (Healy, 2020; Laninga-Wijnen et al, 2022). Our results showed that classroom defending behaviors mitigated the association between social dominance goals and bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Even though defending may be helpful for victims of bullying (Laninga‐Wijnen et al, 2022; Sainio et al, 2011), it is thus far unclear whether bully‐directed forms of defending place defenders themselves at risk. These types of defending go against the goals and behaviors of powerful bullies, and therefore may require a high peer status and be potentially costly in terms of status.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure reliability and validity of peer‐nomination scores, we selected classrooms with at least 10 participating students at all waves ( n = 4376; cf. Laninga‐Wijnen et al, 2022) and with a participation rate of at least 40%, resulting in a sample of 3680 students in 211 classrooms (including 112 seventh‐grade classrooms). Participants were on average 13.94 years of age (SD = 0.74), 53.0% identified themselves as girls, and the majority of participants were born in Finland (83.9%).…”
Section: Methodsmentioning
confidence: 99%